2003
DOI: 10.1161/01.cir.0000101919.00548.86
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain- and Marinobufagenin-Induced Proliferation of Human Umbilical Vein Smooth Muscle Cells and a Rat Vascular Smooth Muscle Cell Line, A7r5

Abstract: Background-We studied the growth-promoting effects of 2 sodium pump-selective cardiotonic steroids, ouabain and marinobufagenin, on cultured cells from vascular smooth muscle (VSMCs) from human umbilical vein and a rat VSMC line, A7r5. Methods and Results-Both ouabain and marinobufagenin activated proliferation of these cells in a concentrationdependent manner, reflecting the cardiotonic steroid sensitivity of the specific ␣ 1 subunit contained within each cell source. The observed effective concentration rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 26 publications
6
75
0
4
Order By: Relevance
“…In addition to maintaining the electrochemical gradient, the Na,K-ATPase has been shown to act as a receptor and signal transducer. Previous reports indicate that Na,K-ATPase signal transduction stimulates proliferation in smooth muscle cells (11) and apoptosis in prostate cancer cells (12). Ouabain, an endogenously synthesized hormone (13,14), is Na,K-ATPase's ligand and forms a hormone-receptor complex capable of inducing mitogen-activated protein (MAP) kinase phosphorylation (15,16) and intracellular Ca 2ϩ signaling (17)(18)(19).…”
mentioning
confidence: 99%
“…In addition to maintaining the electrochemical gradient, the Na,K-ATPase has been shown to act as a receptor and signal transducer. Previous reports indicate that Na,K-ATPase signal transduction stimulates proliferation in smooth muscle cells (11) and apoptosis in prostate cancer cells (12). Ouabain, an endogenously synthesized hormone (13,14), is Na,K-ATPase's ligand and forms a hormone-receptor complex capable of inducing mitogen-activated protein (MAP) kinase phosphorylation (15,16) and intracellular Ca 2ϩ signaling (17)(18)(19).…”
mentioning
confidence: 99%
“…Xie (60) reported that in addition to promoting ion transport, Na ϩ /K ϩ -ATPase acts as a signal transducer in a cell-specific manner. Allen and co-workers (61,62) demonstrated that the cardiotonic steroid ouabain stimulates vascular smooth muscle cell proliferation, which correlates with increased epidermal growth factor transactivation and Src phosphorylation. Moreover, binding of ouabain to the sodium pump induces the phosphorylation of various MAPKs and subsequently activates the transcription factors AP-1 (activator protein-1) and NFB (63).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the primary role of CTS during pregnancy is control of water-electrolyte balance via induction of natriuresis [3]. Growing evidence for implication of CTS including MBG, in tissue growth and differentiation [20,24,25], raises the possibility that the fetus may be a primary target for MBG. Our present data suggest that regulation of carbohydrate metabolism and modulation of glucose tolerance may also be one of the roles of MBG in pregnancy.…”
Section: Discussionmentioning
confidence: 99%